Efektivitas Injeksi Larutan Kapur untuk Menurunkan Plastisitas Tanah Lempung sebagai Upaya Mengatasi Kerusakan Jalan Raya - Sumiyanto Sumiyanto; Arwan Apriyono (Jenderal Soedirman University, 2012)
Highway built on high plasticity clay will be easily damaged by groundshrinkage flower essence. Stabilization of clayby mixing lime is a repairement method that has been proven quite effective. However, this method is difficult to be applied in existing road because demolition must be done. Stabilization of clay using lime solution injection is the method proposed toovercome the problems of expansive clay under the existing highway, therefore demolition is not required. This study was conducted to obtain effective parameters influencing the distance lime solution injection sites and time required for complete stabilization process. This research was conductedin labotarorium by injection experiments. Test results shows indications of soil plasticity decrease, especially the value of plasticity index (PI) and liquid limit (LL). PI decreases from 24.74% to 19.5% and LL decrease from 52.32% to 45%. Based on data analysis it appears that the time required for complete lime solution injection (effective time) has not been obtained in this test. Based on test data, until the day 28 value of soil plasticity index is still low. In this study obtained effective distance influencing the injectionsolution of lime is 100 cm. The distance is still need to be enlarged by increasing the high pressure.